Efeito vasorelaxante da estrona sobre aorta torácica de ratos: contribuição ao estudo do mecanismo de ação - Oliveira, Thiago Sardinha de (2014)
Endogenous estrogens have been associated with greater vascular protection in premenopausal women, and the increased risk of cardiovascular diseases in postmenopausal women can be associated to the decrease in plasma estrogen levels. Furthermore recently studies showed that the use of estrogens, like estrone, exhibits remarkable vascular effect when used on isolated arteries, however any investigation was made to elucidate the mechanism of action of this compound. So, the present study was designed to investigate the ability of estrone to induce vascular relaxation and modulate NO-dependent signaling pathway and analyzed the role of estrogens receptor on estrone-mediated vascular relaxation, compared with the effects promoted by 17β-estradiol. 12 week-old male Wistar rats were used to the vascular reactivity, which was performed in an organ bath study for an isometric tension recording. To the experimental protocols, concentration-response curves (0.1 - 100μM) to estrone or 17β - estradiol were performed. The mechanism contributing to estrone-induced effects were determined comparing with the vascular effects induced by 17β - estradiol that have its effect vascular well characterized. It was observed that the vascular relaxation promoted by estrone is dependent on the endothelium and the estrogen receptor. The vasorelaxant effect promoted by estrone was significantly altered in the presence of the inhibitor of PI3K signaling pathway (wortmannin) and the Ca2+-CaM complex inhibitor (calmidazolium), showing the involvement of PI3K/Ca2+-CaM signaling pathways. This study demonstrate that estrone promoted vasorelaxant effect on rat thoracic aortic on endotheliumdependent manner and its effect depends on the estrogen receptors that activate the PI3K pathway and the Ca2+-calmodulin complex which subsequently activates the NO/cGMP pathway. These results contribute to the better understanding of the role of estrone in the conjugated equine estrogen (CEE) which could be associated to the benefits effects of estrogens in the CEE therapy.